Analysis of the Employed Program of the Philippine Health Insurance Corporation - Denise Valerie Silfverberg (Philippine Institute for Development Studies (PIDS), 2014)
The Employed Program of the Philippine Health Insurance Corporation (PhilHealth) caters to those in the formal sector. Included are those in the government and private sectors with a formal employer-employee relationship. Coverage levels for both the government and private sectors are promising with regional averages of 74 percent and 71 percent, respectively; and provincial averages of 80 percent and 75 percent, respectively. For the private sector, certain sectors were found to be more prone to undercoverage. For the government sector, no clear pattern was found to explain the causes of variation between provinces. This is likely due to the absence of casual and contractual employees in the model. The findings for both sectors are possible propositions on how targeting should be implemented to address the gaps that exist in what is supposed to be a mandatory scheme.
Keywords: 330; health care financing; Philippines; social health insurance; universal coverage; formal sector; employed program